Transient processes of electrical parameters in different modes of operation of air supply systems in the design and testing of aviation equipment - Ільєнко, С.С.; Тихонов, В.В. (Science-based technologies, 2018)
The article is devoted to the research and quality assurance of electrical parameters of modern air-conditioning systems in the conditions of transitional processes in normal, abnormal and emergency modes of operation. The analysis of the composition of the consumers on a modern aircraft, the requirements of international normative and technical documents concerning the parameters of the quality of electrical equipment of the aircraft, the choice of the drive and the generator, taking into account the specific conditions of normal, abnormal and emergency work of the air supply system, as well as in the conditions of the transitional processes, has been carried out. The purpose of the study is realized on the example of the estimation of the quality of electric energy in the channels of the synchronous generator of the aircraft, which shows transient processes at a load value of 50% of rated power, and with a jump-like load change from 50% to 150% of nominal power.